For Putin and for Sharia: Dagestani Muslims and the Islamic State - Kaliszewska, Iwona (NIU Series in Slavic, East European, and Eurasian Studies, 2023)
For Putin and for Sharia -- Contents -- Prologue: Pizza with Shakhidkas -- Introduction -- 1. Political and Social Instability in Dagestan -- 2. Torture, Exorcisms, and Checkpoints: Experiencing the "Fight against Terrorism" -- 3. The Resurgent Importance of Islam in the Everyday Life of Dagestanis -- 4. Wahhabis, Tariqatists, and "New Muslims" -- 5. Sharia: Thinking beyond the (Secular) State? -- Conclusion -- Epilogue -- Acknowledgments -- Notes -- References -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- R -- S -- T -- U -- V -- W -- Y -- Z.